Educating engineers of the future: T-shaped professionals for managing infrastructure projects - Johan Ninan; Marcel Hertogh; Yan Liu (Project Leadership and Society (PLAS), 2022)
Infrastructure projects are costly, colossal, complex, captivating, controversial, and laden with control issues. The development of these projects causes environmental, social, and political disruptions in the local environment, which have to be carefully handled by professionals in the field. This article aims to enhance the performance of infrastructure development professionals by highlighting the necessary competencies and how these competencies can be improved through preparation and training. After discussing the different shapes of professionals, the competencies for infrastructure development are discussed. It is argued that the competencies for infrastructure development are similar to the T-shaped framework. Competencies such as in-depth knowledge, ability to understand and work in different areas, being flexible and adaptive to change, having decision-making capabilities, and willingness to be life-long learners are instrumental in creating T-shaped professionals for infrastructure development. The different learning activities such as lectures, on-site visits, role plays, case study discussions, problem-solving exercises and project work can be employed to educate professionals in the area. The suitability of these methods for online education is also discussed. The study calls for more research to trace the effectiveness of learning activities in the infrastructure sector.
Keywords: 650; T-shaped professionals; Infrastructure projects; Competencies; Activities for learning